The changing relationship between the Chinese Government and Non-governmental Organisations in social service delivery: approaching partnership?. Issue 2 (3rd April 2019) - Gong, Huihui; Jiang, Haiyan; Leung, Joe C. B.
ABSTRACT: Using the Guangzhou social governance reform pilot as a case, this paper aims to explore the transformation of Chinese governments in managing collaborative non-governmental organisation (NGO) relationships. Local governments have adopted multiple new governance tools, and the expansion of the NGO sector with genuine grassroots development has been observed. However, valuable principles of New Public Management (NPM) paradigm have not been followed, and strong authoritarian and bureaucratic practices have been revealed. The state–NGO relationship has moved from a typical statist to a state-corporatist model. Findings indicate distinctive features of Asian public administration and the limitations of applying Westernized NPM models.